1998
DOI: 10.1016/s0014-5793(98)00596-1
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan 272: an essential determinant of crystalline cellulose degradation by Trichoderma reesei cellobiohydrolase Cel6A

Abstract: Trichoderma reesei cellobiohydrolase Cel6A (formerly CBHII) has a tunnel shaped active site with four internal subsites for the glucose units. We have predicted an additional ring stacking interaction for a sixth glucose moiety with a tryptophan residue (W272) found on the domain surface. Mutagenesis of this residue selectively impairs the enzyme function on crystalline cellulose but not on soluble or amorphous substrates. Our data shows that W272 forms an additional subsite at the entrance of the active site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
77
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(86 citation statements)
references
References 31 publications
8
77
1
Order By: Relevance
“…In our recent work, the substitution mutation W267C was found to be a critical mutation for the degradation of crystalline cellulose III I but not of amorphous phosphoric acid-swollen cellulose (Tachioka et al, 2016), which was a similar finding to the work on TrCel6A (Koivula et al, 1998). Trp267 is located at the entrance to the catalytic site at subsite +4 and probably plays a specialized role in the recognition and recruitment of a single cellulose chain from the crystalline surface (Fig.…”
Section: Noncatalytic But Notable Residues Of Pccel6asupporting
confidence: 75%
“…In our recent work, the substitution mutation W267C was found to be a critical mutation for the degradation of crystalline cellulose III I but not of amorphous phosphoric acid-swollen cellulose (Tachioka et al, 2016), which was a similar finding to the work on TrCel6A (Koivula et al, 1998). Trp267 is located at the entrance to the catalytic site at subsite +4 and probably plays a specialized role in the recognition and recruitment of a single cellulose chain from the crystalline surface (Fig.…”
Section: Noncatalytic But Notable Residues Of Pccel6asupporting
confidence: 75%
“…Many mutational studies in which Trp has been replaced with nonaromatic residues have shown negative effects on activity and processivity of, for example, cellulases (16,36,38,(43)(44)(45)(46) and chitinases (47)(48)(49). One suggested role of Trp is that "stacking" interactions of -electrons in its aromatic ring and the ␣-face of the carbohydrate (50) enable the necessary sliding of the bound chain (4, 51), possibly through stabilization of the transition state between adjacent positions in the processive movement (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…One suggested role of Trp is that "stacking" interactions of -electrons in its aromatic ring and the ␣-face of the carbohydrate (50) enable the necessary sliding of the bound chain (4, 51), possibly through stabilization of the transition state between adjacent positions in the processive movement (52,53). Tryptophan residues near the entrance of the active tunnel are also important for the initial "threading" and recognition of the cellulose strand, particularly on crystalline substrates (16,26,38,44,54). In the current work, we used the W38A mutation in T. reesei Cel7A to obtain an enzyme with weakened substrate affinity.…”
Section: Discussionmentioning
confidence: 99%
“…2A). In addition to the steric constraints of the tunnel, carbohydrate-interactions of aromatic residues lining the substrate-binding clefts are important for processivity and, more generally, may make large contributions to the ligand binding free energy (21,22,25,26,28,(62)(63)(64)(65). Notably, ChiC2 has fewer such aromatic residues than ChiA and ChiB, primarily affecting the product subsites (Fig.…”
Section: Discussionmentioning
confidence: 99%